(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
There is a consensus among the scholars that a well-motivated and improves workforce is a panacea to effective and efficient productivity to achieve the organizational objective. This study examines the nexus between human capital development, good governance and effective service delivery in local government system in Nigeria with a particular reference to Ekiti State. The paper adopts theoretical analysis to explain the functional area and justify the existence of local government in Nigeria. The study relied mainly on secondary data backed by practical observation and analytical framework. The central argument is that human capital challenges and lack of financial and administrative autonomy has being the bane of inefficiency at the local government system in Nigeria The paper reveals that lack of quality personnel hindered the effective performance of local government in Nigeria. Equally, the process of chosen its administrative leadership which is more of political patronage, rather than on merit, capability and experience also accounted for mediocrities at the local government administration. The article recommends that in order to enhance a good governance and effective service delivery at the grassroots, there is need for financial and administrative autonomy and a robust human capital development programme for various categories of workers through a well-coordinated efforts of local government service commission and ministry of local government affairs to enhance better service delivery.